2018
DOI: 10.1103/physrevlett.121.178101
|View full text |Cite
|
Sign up to set email alerts
|

Cytoskeletal Anisotropy Controls Geometry and Forces of Adherent Cells

Abstract: We investigate the geometrical and mechanical properties of adherent cells characterized by a highly anisotropic actin cytoskeleton. Using a combination of theoretical work and experiments on micropillar arrays, we demonstrate that the shape of the cell edge is accurately described by elliptical arcs, whose eccentricity expresses the degree of anisotropy of the internal cell stresses. This results in a spatially varying tension along the cell edge, that significantly affects the traction forces exerted by the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
67
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(74 citation statements)
references
References 36 publications
4
67
1
Order By: Relevance
“…19,20 The cell spreading area increases with the substrate stiffness for several cell types, including cardiac myocytes, 17 myoblasts, 18 endothelial cells and fibroblasts, 19 and mesenchymal stem cells. 21 In our previous work 22 we have investigated the shape and traction forces of concave cells, adhering to a limited number of discrete adhesion sites and characterized by highly anisotropic actin cytoskeletons. Using a contour model of cellular adhesion, 8,[23][24][25][26] we demonstrated that the edge of these cells can be accurately approximated by a collection of elliptical arcs obtained from a unique ellipse, whose eccentricity depends on the degree of anisotropy of the contractile stresses arising from the actin cytoskeleton.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…19,20 The cell spreading area increases with the substrate stiffness for several cell types, including cardiac myocytes, 17 myoblasts, 18 endothelial cells and fibroblasts, 19 and mesenchymal stem cells. 21 In our previous work 22 we have investigated the shape and traction forces of concave cells, adhering to a limited number of discrete adhesion sites and characterized by highly anisotropic actin cytoskeletons. Using a contour model of cellular adhesion, 8,[23][24][25][26] we demonstrated that the edge of these cells can be accurately approximated by a collection of elliptical arcs obtained from a unique ellipse, whose eccentricity depends on the degree of anisotropy of the contractile stresses arising from the actin cytoskeleton.…”
Section: Introductionmentioning
confidence: 99%
“…1A). 22 However, the physical origin of these alignment mechanisms is less clear and inevitably leads to a chicken-and-egg causality dilemma: do the stress fibers align along the cell's axis or does the cell elongate in the direction of the stress fibers?…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…by virtue of Eq. (5). Some further detail about the geometry of protrusions in this model can be found in Ref.…”
Section: The Effect Of Bending Elasticitymentioning
confidence: 99%
“…Cells are exposed to several mechanical and physical cues within their three-dimensional microenvironment, to which they respond by exerting forces, regulating their shape, internal cytoskeletal tension, and elastic modulus (1)(2)(3)(4)(5). These complex mechanoresponses are the result of integrated signals from many distinct mechanosensitive structures such as ion channels, focal adhesions, adherens junctions, cytoskeleton, and LINC complex (6,7).…”
Section: Introductionmentioning
confidence: 99%